Hubungan Sumber Informasi, Dukungan Keluarga dan Dukungan Tenaga Kesehatan dengan Minat Ibu Hamil Melakukan Pemeriksaan Triple Eliminasi di Wilayah Kerja Puskesmas Cikeusal Kabupaten Serang Banten - Titin Sumarni; Masluroh Masluroh (Malahayati Nursing Journal, 2023)
ABSTRACT Disease transmission from mother to child can be prevented by early examination of pregnant women which is known as triple elimination of HIV, Hepatitis B and Syphilis. Cikeusal Community Health Center, Serang Banten Regency, 6.81% participated in the Triple Elimination screening. several factors related to the triple elimination examination including sources of information, family support and support from health workers. Knowing the relationship between sources of information, family support and support from health workers with the interest of pregnant women in carrying out triple elimination examinations in the Work Area of the Cikeusal Health Center, Serang Regency, Banten in 2023. This research is a quantitative analytic study with a cross sectional design. The sample in this study were pregnant women who examined pregnant women at the Cikeusal Health Center, Serang Banten Regency, totaling 63 respondents using the accidental sampling technique. The research instrument used a questionnaire. Data is primary data analyzed using square test. The results of univariate analysis showed that pregnant women were not interested in carrying out a triple elimination examination 50.8%, 76.2% obtained information from health workers, 63.5% supported families and 81% supported health workers. The results of the bivariate analysis found that there was a significant relationship between sources of information (p value = 0.022), family support (p value = 0.000) and support from health workers (p value = 0.005) with the interest of pregnant women in carrying out the triple elimination examination. Sources of information, family support and health workers are related to the interest of pregnant women in carrying out triple elimination examinations. It is hoped that health workers can be proactive in providing counseling about the importance of carrying out a triple elimination examination at the time of the first pregnancy check-up. Keywords: Sources of Information, Family Support and Health Workers, Interest in Triple Elimination     ABSTRAK Penularan penyakit dari ibu ke anak dapat dicegah dengan pemeriksaan awal pada ibu hamil yang disebut sebagai triple eliminasi penyakit HIV, Hepatitis B dan Silifis. Puskesmas Cikeusal Kabupaten Serang Banten 6,81% mengikuti screening Tripel Eliminasi. beberapa faktor yang berhubungan dengan pemeriksaan triple eliminasi diantaranya sumber informasi, dukungan keluarga dan dukungan tenaga kesehatan. Mengetahui hubungan sumber informasi, dukungan keluarga dan dukungan tenaga kesehatan dengan minat ibu hamil melakukan pemeriksaan triple eliminasi di Wilayah Kerja Puskesmas Cikeusal Kabupaten Serang Banten Tahun 2023. Penelitian ini merupakan penelitian analitik kuantitatif dengan rancangan cross sectional. Sampel dalam penelitian ini adalah ibu hamil yang melakukan pemeriksaan Ibu hamil di Puskesmas Cikeusal Kabupaten Serang Banten berjumlah 63 responden dengan teknik accidental sampling. Instrumen penelitian menggunakan kuesioner. Data merupakan data primer dianalisis menggunakan uji uji  square. Hasil analisis univariat diketahui ibu hamil tidak berminat melakukan pemeriksaan triple eliminasi 50,8%, mendapatkan sumber informasi dari tenaga kesehatan 76,2%, keluarga mendukung 63,5% dan tenaga kesehatan mendukung 81%. Hasil analisis bivariat diketahui bahwa ada hubungan yang signifikan antara sumber informasi (p value = 0,022), dukungan keluarga (p value = 0,000) dan dukungan tenaga kesehatan (p value = 0,005) dengan minat ibu hamil melakukan pemeriksaan triple eliminasi. Sumber informasi, dukungan keluarga dan tenaga kesehatan berhubungan dengan minat ibu hamil melakukan pemeriksaan triple eliminasi. Diharapkan tenaga kesehatan dapat proaktif dalam memberikan penyuluhan tentang pentingnya melakukan pemeriksaan triple eliminasi pada saat pertama kali melakukan pemeriksaan kehamilan. Kata Kunci: Sumber Informasi, Dukungan Keluarga Dan Tenaga Kesehatan, Minat Triple Eliminasi